CAMTA1, a 1p36 tumor suppressor candidate, inhibits growth and activates differentiation programs in neuroblastoma cells - Henrich, Kai-Oliver; Bauer, Tobias Hartmut; Schulte, Johannes; Ehemann, Volker; Deubzer, Hedwig; Gogolin, Sina; Muth, Daniel; Fischer, Matthias; Benner, Axel; König, Rainer; Schwab, Manfred; Westermann, Frank (Cancer research, 2011)
A distal portion of human chromosome 1p is often deleted in neuroblastomas and other cancers and it is generally assumed that this region harbors one or more tumor suppressor genes. In neuroblastoma, a 261 kb region at 1p36.3 that encompasses the smallest region of consistent deletion pinpoints the locus for calmodulin binding transcription activator 1 (CAMTA1). Low CAMTA1 expression is an independent predictor of poor outcome in multivariate survival analysis, but its potential functionality in neuroblastoma has not been explored. In this study, we used inducible cell models to analyze the impact of CAMTA1 on neuroblastoma biology. In neuroblastoma cells that expressed little endogenous CAMTA1, its ectopic expression slowed cell proliferation, increasing the relative proportion of cells in G1/G0 phases of the cell cycle, inhibited anchorage-independent colony formation, and suppressed the growth of tumor xenografts. CAMTA1 also induced neurite-like processes and markers of neuronal differentiation in neuroblastoma cells. Further, retinoic acid and other differentiation- inducing stimuli upregulated CAMTA1 expression in neuroblastoma cells. Transciptome analysis revealed 683 genes regulated on CAMTA1 induction and gene ontology analysis identified genes consistent with CAMTA1-induced phenotypes, with a significant enrichment for genes involved in neuronal function and differentiation. Our findings define properties of CAMTA1 in growth suppression and neuronal differentiation that support its assignment as a 1p36 tumor suppressor gene in neuroblastoma. Cancer Res; 71(8); 3142-51. ©2011 AACR.
Gesehen am 12.10.2022